Using on-demand dry ice production as an alternative cryogenic cold chain for bovine artificial insemination outreach in low-resource settings1. Issue 2 (3rd February 2020) - Kuiper, Mark; Spencer, Maribeth; Kanyima, Benon M; Ng, Chin H; Newell, Mark; Turyahikayo, Silver; Makoni, Nathaniel; Madan, Damian; Lieberman, Daniel H
Abstract: Artificial insemination (AI) is widely used in livestock industries to breed for desirable characteristics and increase yields. The standard practice of storing and transporting bovine semen uses liquid nitrogen (LN), a scarce commodity in many regions of the world. This study explored the feasibility of using dry ice, a more readily available alternative. We developed equipment that dispenses dry ice from widely available liquid carbon dioxide (LCO2 ) tanks into an easily transportable device. In vivo fertility results with a dry ice cold chain showed no statistical difference to the conventional LN method. In vitro bovine semen analyses also showed that storage under these conditions minimally affects characteristics associated with fertility. A dry ice cold chain system could leverage the global availability of LCO2 to expand the reach of AI and other cold storage applications of biological materials in low-resource settings.